Considering a different model for the Family and Children Courthouse Building. Reflections on the Portuguese experience - Patrícia Branco (Oñati Socio-Legal Series)
Courthouse buildings do not usually play a significant role in most socio-legal research on law-and-courts; and where the courthouse buildings have been considered, authors often take for granted the need for a ritualized adjudicative process within a certain kind of building, usually a pompous and prominent one. My aim, nevertheless, is to discuss the law buildings, and their internal configuration, where the specialized jurisdiction of family and children justice is rendered, in Portugal. This article will thus consider the discrepancies between the courthouses in books and the courthouses in action, or how they are legally designed and concretely structured, and lived, by giving voice to court professionals (judges and prosecutors) and court users, pointing out the problems and needs they have identified, and the claims they make.